Women and domestic violence law in India: a quest for justice - Nigam, Shalu (Routledge, 2020)
Introduction -- Conceptualizing Domestic Violence -- Legislating the Laws Relating to Domestic Violence -- Fighting Against Domestic Violence: Weaving Stories of Pain and Courage -- Women's Experiences with the Law and the Legal System -- The Economics of Love: Women's Rights within Families and Changing Economic Paradigm -- Adjudicating Domestic Violence in Courts -- Conclusion : How Easy is Access to Justice?